2017
DOI: 10.1177/1941738116685299
|View full text |Cite
|
Sign up to set email alerts
|

No Clinically Significant Difference Between Adult and Pediatric IKDC Subjective Knee Evaluation Scores in Adults

Abstract: Background:Two versions of the International Knee Documentation Committee (IKDC) Subjective Knee Evaluation form currently exist: the original version (1999) and a recently modified pediatric-specific version (2011). Comparison of the pediatric IKDC with the adult version in the adult population may reveal that either version could be used longitudinally.Hypothesis:We hypothesize that the scores for the adult IKDC and pediatric IKDC will not be clinically different among adult patients aged 18 to 50 years.Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…To our knowledge, for this demographic the IKDC is the only known adult PROM that has been secondarily shown to be translatable to the pediatric version in adolescent athletes. 45 In a study by Oak et al, 38 the adult and pediatric forms of the IKDC were shown to be significantly different by 1.5 points, although this difference was not clinically significant. The authors concluded that the adult version of the IKDC could be used in adolescents aged 13 to 17 years.…”
Section: Discussionmentioning
confidence: 95%
“…To our knowledge, for this demographic the IKDC is the only known adult PROM that has been secondarily shown to be translatable to the pediatric version in adolescent athletes. 45 In a study by Oak et al, 38 the adult and pediatric forms of the IKDC were shown to be significantly different by 1.5 points, although this difference was not clinically significant. The authors concluded that the adult version of the IKDC could be used in adolescents aged 13 to 17 years.…”
Section: Discussionmentioning
confidence: 95%
“…[5][6][7]16,26,49,50 To our knowledge, of these 6 PROMs, only the Marx activity, IKDC, and Kujala scores have shown some validity for use in pediatric patients. 23,50,54 Even so, these scores are not necessarily the preferred methods of reporting. Shirazi et al 50 evaluated the validity of the Marx activity score in pediatric patients and found the score appeared to be useful only in patients older than 14-thus limiting the score's overall usefulness in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…The IKDC form, meanwhile, exists in an adult and a pediatric version. While no clinically significant difference has been shown between the adult and pediatric versions, 43,54 as Brusalis et al 7 point out in their study of pediatric anterior cruciate ligament postsurgical outcomes, children have a difficult time understanding many of the IKDC concepts. 24 This suggests that, when possible, the IKDC pediatric form should be used in pediatric populations.…”
Section: Discussionmentioning
confidence: 99%
“…4,10,19 A 10-minute washout period was chosen per similar studies comparing the standard IKDC-SKF and the pediatric IKDC. 19,21…”
Section: Methodsmentioning
confidence: 99%